US Hegemony and Latin American Regional Security : The United States’ hegemony in the Organisation of American States (OAS) : Implications for Latin American Regional Security - Isike, Christopher (University of Pretoria, 2022)
Mini-dissertation (MSS (Political Sciences))--University of Pretoria, 2021